2010
DOI: 10.1111/j.1467-8624.2010.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Categorization Among Preschool Children: Increasing Utilization of Sexually Dimorphic Cues

Abstract: Two studies examined how children between ages 4 and 6 use body shape (i.e., the waist-to-hip-ratio [WHR]) for sex categorization. In Study 1 (N=73), 5- and 6-year-olds, but not 4-year-olds, selected bodies with increasingly discrepant WHRs to be "most like a man" and "most like a woman." Similarly, sex category judgments made by 5- and 6-year-olds, but not 4-year-olds, varied with WHR. In Study 2 (N=41), eye movements indicated the functional use of waist and hips in sex categorization. Visual scanning behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
16
2
Order By: Relevance
“…First, at the very least, waists and chests are sexual because they differentiate people on the basis of biological sex. For example, eye‐tracker studies confirm that people focus on men and women's waists and chests when they engage in gender categorization (Hewig, Trippe, Hecht, Straube, & Miltner, ; Johnson, Lurye, & Tassinary, ; Johnson & Tassinary, ). Second, although genitalia may be regarded as more explicitly sexual than waists and chests, they are rarely revealed in interactions with other people, and thus, people use secondary (versus primary) sex characteristics, including waists and chests, as proxies for reproductive fitness (Singh, ).…”
Section: Are Women's Bodies Reduced To Their Sexual Body Parts In Thementioning
confidence: 99%
“…First, at the very least, waists and chests are sexual because they differentiate people on the basis of biological sex. For example, eye‐tracker studies confirm that people focus on men and women's waists and chests when they engage in gender categorization (Hewig, Trippe, Hecht, Straube, & Miltner, ; Johnson, Lurye, & Tassinary, ; Johnson & Tassinary, ). Second, although genitalia may be regarded as more explicitly sexual than waists and chests, they are rarely revealed in interactions with other people, and thus, people use secondary (versus primary) sex characteristics, including waists and chests, as proxies for reproductive fitness (Singh, ).…”
Section: Are Women's Bodies Reduced To Their Sexual Body Parts In Thementioning
confidence: 99%
“…Such a possibility is supported by the findings that even much older children sometimes fail in tasks in which they are required to explicitly link cues with sex categories. For example, in Johnson et al (2010), even 4-year-olds failed to associate waist-to-hip ratios with sex categories, something that older children and adults readily do.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and Bentler (1971) reported that 4- to 6-year-old children use hair and body type (muscularity, shape) to discriminate between males and females. Johnson, Lurye, and Tassinary (2010) found that 5- and 6-year-olds use the waist-to-hip ratio (WHR) for sex identification but 4-year-olds do not. Thus, children begin to associate different cues such as hair length, body type, and WHR to males and females at different ages.…”
mentioning
confidence: 99%
“…(ii) Materials and procedure Stimuli included 21 computer-generated bodies [4,19,20] that varied in a sexually dimorphic cue, the waist-to-hip ratio (WHR; figure 1). …”
Section: Study 1 (A) Methods (I) Participantsmentioning
confidence: 99%